Skogsbrandens påverkan på död ved - Karlsson, Maria (2007)
Fire is an important ecological factor, but its consumption of coarse woody debris, CWD, has hardly received any attention. In this study, I investigate the consumption in relation to the time of initial flame exposure and propensity for continued combustion of standing CWD of pine (Pinus sylvestris). Two types of CWD were studied. Firstly, wood that had been dead for one to ten years. Secondly, wood that had been dead for several decades. In the burning experiments, logs of approx. 1 meter were exposed to fire while standing. Small-diameter branches and twigs were used as fuel to simulate a passing flame front. Exposure time (flame contact with the wood) was varied to facilitate comparisons of combustion depths and studies of fire behaviour. A distinct relation between the time that the wood was exposed to flames and the combustion depth could be seen. On average, the combustion depth was approx. 1 mm per minute of exposure. For longer exposures (>10 min), this speed decreased markedly, probably due to the layer of charcoal acting as an insulator against continued charring. Wood with high levels of resin burned deeper. Also, wood with rotten sapwood got a deeper combustion layer, possibly due to better air supply into the wood. After the exposure from external flames stopped, the cases of continued combustion in the wood were rare. This occurred mainly in the form of smouldering combustion and went extinct within a short time for most of these cases, without much wood consumed. This smouldering combustion turned into flaming combustion under certain conditions. The experiments showed that rotten wood, splintered wood and cavities within the wood are of great significance for the fire to remain alive. Together with air supply this determines the extent of the continued combustion and thus the loss of wood.